Identifikasi Arsitektur Fasade Art Deco Dikaitkan Dengan Fungsi Bangunan Museum - Dwipa, Novantio; R. Sukardi, Rahy; Astrid Hartoety, Dianna (CV RIFAINSTITUT, 2024)
Indonesia has many architectural styles, the biggest cause of architectural development in Indonesia was the colonial events carried out by Europeans and Japanese. The city of Bandung is called